Students’ Perceptions on the Use of Social Media for Learning English Based on Technology Acceptance Model (TAM) - Khairiyah Nadhifa; Dinovia Fannil Kher (Journal of English Language Teaching, 2022)
The activity of English language learning does not just happen inside of the class but also it happens outside of the classroom where learning occurs independently. Social media is considered as a source of online material that can play a key role in the teaching and learning field. This research aimed to know students’ perceptions on the use of social media for learning English based on Technology Acceptance Model (TAM) seen from two indicators; Perceive Ease of Use (PEOU) and Perceive Usefulness (PU). The populations of this research were the students of the 3rd grade at SMP Negeri 22 Padang in the 2022/2023 academic year. Simple random sampling was used in this research where the total sample was 63 students. This research was a descriptive study where quantitative approach was used to analyse the data. Based on the data that taken from the questionnaire as an instrument, it can be concluded that using social media for learning English based on Technology Acceptance Model (TAM) provided positive perceptions by the students. Students also perceived positive perceptions for the ease of use and the usefulness in the context of learning English using social media. It is shown by the result provided from the questionnaire.